650 mW/mm output power density of H‐terminated polycrystalline diamond MISFET at 10 GHz. Issue 7 (1st March 2020) - Yu, Cui; Zhou, Chuang Jie; Guo, Jian Chao; He, Ze Zhao; Wang, Hong Xing; Cai, Shu Jun; Feng, Zhi Hong
Abstract : In this work, metal–insulator–semiconductor field effect transistors (MISFET) with gate length of 350 nm were fabricated on hydrogen‐terminated polycrystalline diamond by a self‐aligned process. Aluminium film with thickness of 2 nm was evaporated on the sample and formed self‐oxidised alumina to act as the gate dielectric. The devices show good direct current and radio frequency performances with a maximum frequency of oscillation ( f max ) of 34 GHz and continuous‐wave output power density of 650 mW/mm at 10 GHz.